Sooraj Mukhi class 7th urduka guldasta text book - Fozia Ehsaan farooqi; Fozia Ehsaan Farooqi (Lahore Oxford press, 2024)
t is a very nice textbook with multiple stories and poems. it has stories about many pakistani heroes, fights, and victories. It teaches alot of things ...